Pengaruh Google Class Room Terhadap Pemahaman Siswa Pada Pelajaran Bahasa Indonesia - Uray Ferry Haryanto; Mega Riyawati (PT. ALHAFI BERKAH INDONESIA, 2023)
The use of the Google Classroom Application is a free online service for schools, non-profit institutions, and anyone who has a Google account, used for online learning media by students and teachers to stay connected both inside and outside the classroom and is an alternative used during the Covid pandemic -19. The results showed that the use of the Google Classroom Application reached 83.2%. This was evident from the results of the questionnaire data which reached 83.2% which was in the range of 81% -100% which was categorized as Very Good. Student understanding reached 76.4%. This is evident from the results of the questionnaire data reaching 76.4% which is in the range of 61% -80% which is categorized as Good. The influence of the teacher's use of the Google Classroom Application on students' understanding of the Indonesian language subject in class IX at SMPIT Al-Madinah Tanjungpinang, the calculation results obtained rxy = 0.4824 which is between values ​​(0.40 – 0.70). Thus rxy = 0.4824 is greater than r table at a significant level of 5% and a significant level of 1% (0.2352 <0.3060 <0.4824) this means that Ha is accepted and Ho is rejected. So the results of the correlation analysis show that there is an effect of the teacher's use of the Google Classroom Application on students' understanding of Indonesian in class IX SMPIT Al-Madinah Tanjungpinang.